2016
DOI: 10.1038/srep20210
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Circulating Tumor Cells in Head and Neck Squamous Cell Carcinoma: a systematic review and meta-analysis

Abstract: Several techniques have been developed to detect circulating tumor cells (CTC) in patients with head and neck squamous cell carcinoma (HNSCC), but their diagnostic and prognostic value are not yet fully established. A computerized retrieval of literatures was conducted without time restrictions using the electronic database in December 2014. Diagnostic accuracy variables were pooled and analyzed by the Meta-DiSc software. Engauge Digitizer and Stata software were used for pooled survival analysis. Twenty-two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 72 publications
(135 reference statements)
3
70
0
Order By: Relevance
“…Therefore, once CTCs are detected, the patients should be considered as having distant metastasis or high tumor burden. The result was similar to that of a meta‐analysis which reported low sensitivity of 24.6% and a high specificity of 100% of CTCs in head and neck squamous cell carcinomas . In contrast, a high sensitivity of EBV DNA was observed in NPC prompting us to construct a model combining EBV DNA and CTCs to develop a more sensitive and precise tool.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, once CTCs are detected, the patients should be considered as having distant metastasis or high tumor burden. The result was similar to that of a meta‐analysis which reported low sensitivity of 24.6% and a high specificity of 100% of CTCs in head and neck squamous cell carcinomas . In contrast, a high sensitivity of EBV DNA was observed in NPC prompting us to construct a model combining EBV DNA and CTCs to develop a more sensitive and precise tool.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, markers from liquid biopsies that are directly related to cancer cells or cancer‐produced molecules have been employed, including circulating tumor cells (CTCs), cell‐free DNA (cfDNA)/circulating tumor DNA (ctDNA), cfRNA, and exosomes . It is generally accepted that CTCs may play an important role in cancer metastasis .…”
Section: Biomarkers From Liquid Biopsiesmentioning
confidence: 99%
“…188 However, some are not always cancer-specific, giving rise to problems in distinguishing between malignant and inflammatory disease. [189][190][191][192] More recently, markers from liquid biopsies that are directly related to cancer cells or cancer-produced molecules have been employed, including circulating tumor cells (CTCs), 147,[150][151][152][153][154][155][156][157][158][159][160][161][162][163][164]193,194 cell-free DNA (cfDNA)/ circulating tumor DNA (ctDNA), [187][188][189][190][191][192]195,196 cfRNA, 184 and exosomes. [196][197][198] It is generally accepted that CTCs may play an important role in cancer metastasis.…”
Section: Biomarkers From Liquid Biopsiesmentioning
confidence: 99%
“…The study also suggested that the presence of CTCs could act as an indicator for treatment response (Huang et al, 2015). Apart from these studies, promising correlations of the presence of CTCs with head and neck (Wu et al, 2016), bladder cancers (Gazzaniga et al, 2014) were also reported by different groups. Although lung cancer mortality is a major clinical concern, however, the correlation of CTCs with lung cancer detection was less predictive at least with current sets of methods, which mostly rely on use of epithelial marker to identify CTCs.…”
Section: Approaches Used To Detect Metastatic Lesions (On a Clinicmentioning
confidence: 90%